THE STATE POSITION AS A PREFERENT CREDITOR OF THE TAX DEBT IN BANKRUPTCY - Damayanti, Ratih (JOURNAL OF PRIVATE AND COMMERCIAL LAW, 2018)
Bankruptcy is a decision issued by the Court that resulted in a general confiscation of all the wealth owned and the wealth that will be owned by the debtor in the future. The State has the preference right to tax debt on the property of the Taxpayer. This means that the position of the state as a preferent creditor who is declared to have prior rights over the property of the Taxpayer to be auctioned in public. The state's preference by taxpayer repayment is in fact not as easy as one might imagine, there are some problems. The purpose of article writing is to know the position of the State as a preferent creditor for the tax debt of the taxpayer declared bankrupt and know the obstacles of the State as a preferent creditor to the repayment of tax debt on taxpayers declared bankrupt. Provisions on the State's prior rights include the principal taxes, administrative sanctions in the form of interest, penalties, increases, and tax collection fees. The weakness in the regulation creates an impediment to the application of the State as a preferential creditor who has the preference right, namely the formulation of the preference right itself that is unclear about the notion of the state's position as the preferent creditor, in addition to the overlapping regulation of the preference right (preferent creditor) The Civil Code, the Law on General Taxation and Bankruptcy Laws and Postponement of Debt Payment Obligations which not only the State as the Preference rights holder's creditors.